Avaliação mimética da atividade catalítica da superóxido dismutase e efeitos citotóxicos de complexos de cobre derivados de aminas de furanos e tiofenos. - Pellegrin, Sidnei Flores de (2019)
This work evidences the synthesis, characterization, evaluation of superoxide dismutase mimetic catalytic activity, and cytotoxic effects of copper complexes. The complexes were obtained from aldol condensation between aromatic amines (furfurylamine, 2-thiopheneethylamine, and 2-thiophenomethylamine) and aromatic aldehydes (salicylic aldehyde, ortho-vanillin, and pyridoxal hydrochloride). The complexes were structurally characterized by X-ray diffraction, cyclic voltammetry, infrared, Raman, and ultraviolet/visible spectroscopic methods. Subsequently, the compounds were submitted to NBT (nitrotetrazolium chloride blue) photoreduction methodology to quantify antioxidant activity. The best results were evidenced for complexes containing pyridoxal derivatized. In addition, the complexes were tested for possible cytotoxic effects in cells, such as DNA-PicoGreen® reagent fluorimetric methodologies, MTT technique, dichlorofluorescein diacetate test (DCFH-DA), and nitric oxide assay.